Active LifestyLe Rehabilitation Interventions in aging Spinal Cord injury (ALLRISC): a multicentre research program. (June 2013) - van der Woude, L. H. V.; de Groot, S.; Postema, K.; Bussmann, J. B. J.; Janssen, T. W. J.; ,; Post, M. W. M.
<x xml:space="preserve">Abstract</x> Background: With today's specialized medical care, life expectancy of persons with a spinal cord injury (SCI) has considerably improved. With increasing age and time since injury, many individuals with SCI, however, show a serious inactive lifestyle, associated with deconditioning and secondary health conditions (SHCs) (e.g. pressure sores, urinary and respiratory tract infections, osteoporosis, upper-extremity pain, obesity, diabetes, cardiovascular disease) and resulting in reduced participation and quality of life (QoL). Avoiding this downward spiral, is crucial. Objectives: To understand possible deconditioning and SHCs in persons aging with a SCI in the context of active lifestyle, fitness, participation and QoL and to examine interventions that enhance active lifestyle, fitness, participation and QoL and help prevent some of the SHCs. Methods: A multicentre multidisciplinary research program (Active LifestyLe Rehabilitation Interventions in aging Spinal Cord injury, ALLRISC) in the setting of the long-standing Dutch SCI-rehabilitation clinical research network. Results: ALLRISC is a four-study research program addressing inactive lifestyle, deconditioning, and SHCs and their associations in people aging with SCI. The program consists of a cross-sectional study (n = 300) and three randomized clinical trials. All studies share a focus on fitness, active lifestyle, SHCs and deconditioning and outcome measures on these and other (participation, QoL) domains. It is hypothesized that a self-management program, low-intensity wheelchair exercise and hybrid functional electrical stimulation-supported leg and handcycling are effective interventions to enhance active life style and fitness, help to prevent some of the important SHCs in chronic SCI and improve participation and QoL. Conclusion: ALLRISC aims to provide evidence-based preventive components of a rehabilitation aftercare system that preserves functioning in aging persons with SCI.